THE INFLUENCE OF PARENT’S ECONOMIC STATUS, THE NEED FOR ACHIEVEMENT AND ENTREPRENEURSHIP EDUCATION ON INTEREST IN THE FACULTY OF ECONOMICS BAITURRAHMAH PADANG ENTREPRENEURSHIP - Febriani, Rina (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
Baiturrahmah Padang University was established in 1994 as a forum for three high schools that had been established previously, namely the faculty of economics (1985), the faculty of dentistry (1985), the faculty of medicine (1993), then in 1999 another faculty was opened, the faculty of public health. The University of Baiturrahmah has an address on Jl.raya by pass km.15 aie Pacah, Koto Central, Padang, West Sumatra. This type of research is a quantitative descriptive study with a cross-sectional approach. The population in this study were all students of the faculty of economics 2015-2017 as many as 375 people and a sample of 100 people. The data used are primary data and data analysis used is multiple linear regression analysis. The results found a regression coefficient of economic status variables of parents with a value of t count 2.256 and the value (sig = 0.026 <0.05), then the economic variables of parents have a positive effect on the interest of students of the Baiturrahmah Economic Faculty of entrepreneurship. The regression coefficient of the variable need for achievement with a t value of 0.471 and value (sig = 0.639> 0.05), then the variable need for achievement has no effect on the interest of students of the economics faculty of Baiturrahmah Padang entrepreneurship. The regression coefficient of the entrepreneurship education variable with a t value of 2.309 and the value (sig = 0.023 <0.05) then the entrepreneurship education variable has a positive effect on the interests of students of the economics faculty of Baiturrahmah Padang entrepreneurship. F value of 2.915> 2.70 or (Fcount> Ftable) with a significance value of 0.038 <0.05. This means that the economic status of parents, the need for achievement, entrepreneurship education together affect the interest of students of the economics faculty of Baiturrahmah Padang entrepreneurship.